Meta-analysis of randomized controlled trials on efficacy and safety of extended thienopyridine therapy after drug-eluting stent implantation - Tang, Wenyi; Yeh, James; Chen, Jian; Liu, Mao; Ke, Jianting; Tan, Guangyi; Lin, Xiufang; Wu, Wei (Cardiovascular Diagnosis and Therapy; Vol 6, No 5 (October 01, 2016): Cardiovascular Diagnosis and Therapy, 2016)
Background: The potential benefits and risks of extended thienopyridine therapy beyond 12 months after drug-eluting stent (DES) implantation remain unclear. Methods: Randomized controlled trials (RCTs) were searched in PubMed, EMBASE, the Cochrane Library and China National Knowledge Infrastructure databases. The adverse clinical endpoints were compared between 12 months group (aspirin alone) and >12 months group (additional thienopyridine plus aspirin after 12-month dual antiplatelet therapy). Odds ratios (ORs) with 95% confidence intervals (95% CIs) were used as summary statistics. A random-effect model was used in the meta-analysis process. Results: Finally, three RCTs incorporating 16,265 participants were included in this meta-analysis. The results indicated that the incidences of myocardial infarction (1.55% vs. 2.90%; OR =0.58; 95% CI, 0.40–0.84; P=0.004) and stent thrombosis (0.32% vs. 0.98%; OR =0.35; 95% CI, 0.20–0.62; P12 months group were significantly lower than the 12 months group. However, compared to the 12 months group, the extended thienopyridine therapy markedly increased the risk of bleeding events (2.09% vs. 1.28%; OR =1.64; 95% CI, 1.23–2.17; P